Mechanisms of stroke protection by physical activity - Endres, Matthias; Gertz, Karen; Lindauer, Ute; Katchanov, Juri; Schultze, Jörg; Schröck, Helmut; Nickenig, Georg; Kuschinsky, Wolfgang; Dirnagl, Ulrich; Laufs, Ulrich (Annals of neurology, 2003)
Regular physical activity is associated with a decrease of cerebrovascular and cardiovascular events, which may relate to enhanced endothelium-dependent vasodilation. Here, we provide evidence that physical activity protects against ischemic stroke via mechanisms related to the upregulation of endothelial nitric oxide synthase (eNOS) in the vasculature. Voluntary training on running wheels or exercise on a treadmill apparatus for 3 weeks, respectively, reduced cerebral infarct size and functional deficits, improved endothelium-dependent vasorelaxation, and augmented cerebral blood flow in wild-type mice. The neuroprotective effects of physical training were completely absent in eNOS-deficient mice, indicating that the enhanced eNOS activity by physical training was the predominant mechanism by which this modality protects against cerebral injury. Our results suggest that physical activity not only decreases stroke risk, but also provides a prophylactic treatment strategy for increasing blood flow and reducing brain injury during cerebral ischemia.